Disturbance Rejection Experimental In 3D INTECO Gantry Crane System Via PID-VSC Tuned By PFPSO - Syed Hussien, Sharifah Yuslinda; Ghazali, Rozaimi; Jaafar, Hazriq Izzuan; Chong, Chee Soon (Taylor’s University, 2017)
Gantry Crane System (GCS) is a mechanism in heavy engineering that moves payload from one point to another. Commonly, an experienced operator is required to control the trolley position manually while minimizing the payload oscillation. The transferring process should be done with careful and concentration to ensure the safety environment. Thus, in order to ensure the safety condition, a control strategy of Proportional-Integral-Derivative and Variable Structure Control (PID-VSC) is implemented in the 3D INTECO GCS. The Proportional-Integral-Derivative (PID) controller is used to control the trolley position while the Variable Structure Control (VSC) is used to control the payload oscillation. The parameters of the controllers are defined by Priority-based Fitness Particle Swarm Optimization (PFPSO). The performances are compared to the Proportional-Integral-Derivative and Proportional-Derivative (PID-PD) controller tuned by PFPSO in terms of the precision of trolley position with the minimization of payload oscillation. The robustness of the controller is verified by the injection of internal disturbance in gantry crane system. With the proposed controller, the experimental of 3D INTECO GCS shows that the system is capable of minimizing the payload oscillation while achieving satisfactory trolley position tracking.